Magnesium and Aluminum Oxides Formation Via Conversion Coating of Magnesium Metal in Alcl3/Urea Room Temperature Ionic Liquid - Abood, Hadi. M A; Alwan, Rasha H (Al-Nahrain Journal of Science, 2017)
A highly adherent conversion coating has fabricated on pure magnesium by the treatment with AlCl3/urea room temperature ionic liquid. The conversion coated surface was characterized by Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), Energy Dispersive X-ray analysis (EDXA), and X-ray diffraction. The corrosion resistance of the uncoated and coated Mg metal was evaluated in 3.5 wt% NaCl solution. The coating was homogenous, rough, and was covered the entire magnesium substrate surface. The resulted coating was achieved in 40 min at room temperature as thin films of about 5µm thickness and composed of Al2O3 and magnesium aluminum mixed oxide. Polarization study of the coated specimen showed decreasing in the corrosion potential with remarkable lowering of the corrosion current comparing to that of bare Mg metal.